Correlation of clinical examination, ultrasound, magnetic resonance imaging and arthroscopy as diagnostic tools in shoulder pathology - Biswas, Sondipon; Kanodia, Naman; Tak, Rajat; Agrawal, Siddharth; Roy, Kiran Shankar (International Journal of Research in Orthopaedics, 2020)
Background: Shoulder pathologies can cause significant pain, discomfort, and affect the activity of daily living. The aim of this study was to compare the efficacy of clinical examination, ultrasound, magnetic resonance imaging (MRI) with shoulder arthroscopy in diagnosing various shoulder pathologies, considering shoulder arthroscopy as the gold standard tool. Methods: This was a prospective, comparative study conducted over 35 patients, between 18-75 years of age presenting with chronic shoulder pain or instability of more than 2 months duration. All patients were examined clinically, followed by high resolution ultrasound, MRI, arthroscopy of the affected shoulder. Results: The sensitivity and specificity of ultrasonography (USG) for diagnosing full thickness tear was 100% each and for MRI was 88% and 100% respectively. For subacromial impingement USG had sensitivity of 66.67%, specificity of 94.12%, positive predictive value of 50% and negative predictive value of 88.89%. For rotator cuff tear USG had sensitivity of 92.86%, specificity of 50%, positive predictive value of 81.25% and negative predictive value of 75% considering shoulder arthroscopy as gold standard. Conclusions: USG and MRI both are sensitive techniques for diagnosing of rotator cuff pathologies. USG has high accuracy in diagnosing partial thickness tears as compare to MRI. MRI proved to be superior in estimation of site and extent of tear. Considering shoulder arthroscopy as gold standard, it can be reserved for patients with suspicious of USG/MRI findings or those who may need surgical intervention simultaneously.